... Abyście się wzmacniali i przedłużali życie na ziemi. Eschatologia doskonałości, rygory Nidda i skandal higieny rasowej w okresie 1850–1945 - Nowak, Ewa (ETHICS IN PROGRESS, 2016)
The formation and development of khalachic rules, in particular niddah, was always already oriented towards integral perfectibility of human life. The paper explores the integral life eschatology in Judaism and shows how Niddah has been manipulated by race hygienists and eugenicists 1850–1945 as a tool creating a myth of Jewish race on the one hand, and a counter-myth of the new superhuman race. That scandalous manipulation should be concidered when seeking analogies between the Jewish ideal of integral perfectibility and the Western eugenics.